A Conceptual Framework: Organizational Learning, Competencies, and Innovation in Indonesian Digital Startup - Tambunan, Sihar Tigor Benjamin; Christiananta, Budiman; Rachmawati, Dyna (International Journal of Scientific Research and Management (IJSRM), 2019)
Disruptions carried out by digital startups show a big role of technology-based competencies and  innovations. In fact, both are the results of organizational learning. This paper explores a conceptual framework that links organizational learning with performance through competency development and innovation in Indonesian digital startups. A combination of literature studies on organizational learning and some previous research compared with a number of factual conditions of digital startups in Indonesia, resulting in intended conceptual framework.The authors managed to place technology as a prominent element in each of the proposed variables forming a conceptual framework that links organizational learning with digital startup performance. This conceptual study does not compare the concepts of organizational learning and individual learning in digital startups. Supporting facts used in this study are multi-sector digital startups. So this conceptual framework could be different if applied to specific sectors.Conceptually, organizational learning has the potential to significantly influence the competency development and innovation in Indonesian digital startups.